2013
DOI: 10.9775/kvfd.2012.8474
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Rosemary (Rosmarinus officinalis L.) Oil Supplementation on Performance, Carcass Traits and Some Blood Parameters of Japanese Quail Under Heat Stressed Condition

Abstract: SummaryIn this study, the effects of rosemary (Rosmarinus officinalis L.) oil supplementation to diet were investigated on performance, carcass traits and some blood parameters of Japanese quails exposed to a high ambient temperature of 34°C. A total of 180 fifteen-day-old quails were divided into 6 treatments consisting of 10 birds of 3 replicates. All groups were balanced according to initial live weight and gender. Birds were kept in wire cages in temperaturecontrolled room at either 22°C for 24 h/d (thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Animals under heat stress tend to diminish their heat production by limiting feed intake, with subsequent detrimental effects on live weight gain. Several researchers have also reported that HS decreased the live weight gain (Siegel, 1995;Çiftçi et al, 2013). Golden quail had higher live weight from the beginning of the trial and higher live weight gain at the end of trial.…”
Section: Discussionmentioning
confidence: 93%
“…Animals under heat stress tend to diminish their heat production by limiting feed intake, with subsequent detrimental effects on live weight gain. Several researchers have also reported that HS decreased the live weight gain (Siegel, 1995;Çiftçi et al, 2013). Golden quail had higher live weight from the beginning of the trial and higher live weight gain at the end of trial.…”
Section: Discussionmentioning
confidence: 93%
“…Abd El-Latif et al (2013) exhibited that 100 or 200 mg rosemary oil /kg was not indicated significantly changes in serum levels of total protein, while AST concentration was significantly (P≤ 0.01) decreased. ÇİFTÇİ et al (2013) watched that birds kept in heat stress conditions had a more prominent glucose level than hens kept in thermo neutral condition and dietary rosemary oil had a positive effect on blood glucose level. This finding shows that the rosemary oil might be producing its hypoglycemic action by a component free from insulin secretion by the inhibition of endogenous glucose production or the inhibition of intestinal glucose absorption (Eddouks et al, 2003).…”
Section: Serum Biochemistry Parametersmentioning
confidence: 99%
“…Several nutritional approaches using safe and natural feed additives have been suggested. In this respect, many studies have shown that antioxidant nutrients supplementation in their synthetic (vitamins, minerals) or natural (herbs, spices) form can be used to improve productivity [5] , enhance nutrient availability and prevent against detrimental effect of heat stress [6,7] .…”
Section: Introductionmentioning
confidence: 99%